2020
DOI: 10.33160/yam.2020.08.011
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Bidet Use on Severity of Constipation and Quality of Life Among Pregnant Women

Abstract: Background Constipation is a common problem in pregnancy. This study aims to elucidate the efficacy of using a bidet before defecation to reduce the severity of constipation and improve the quality of life in pregnancy. Methods The sample consisted of an experimental group (n = 30) and a control group (n = 30), a total of 60 pregnant women. Randomization was performed using the pitch-and-toss method from simple probability randomization methods. The research data were collected using the Personal Information F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
(44 reference statements)
0
2
0
Order By: Relevance
“…In a study by Shigematsu et al [6] of 18 patients who had undergone hysterectomy, 15 (83%) of the patients reported smooth bowel movement during the postoperative period when using the bidet toilets. In a study of pregnant women in Turkey, the group that washed their anus before defecation reported a significant improvement in constipation scores compared with the control group, despite not using electric bidet toilets [7].…”
Section: Introductionmentioning
confidence: 97%
“…In a study by Shigematsu et al [6] of 18 patients who had undergone hysterectomy, 15 (83%) of the patients reported smooth bowel movement during the postoperative period when using the bidet toilets. In a study of pregnant women in Turkey, the group that washed their anus before defecation reported a significant improvement in constipation scores compared with the control group, despite not using electric bidet toilets [7].…”
Section: Introductionmentioning
confidence: 97%
“…Using BTS helps in lowering chances of hand contami-nation. It also promotes defecation during pregnancy and among elderly nursing home residents and people with spinal injuries (Oie et al, 2018;Alan et al, 2020;Uchikawa et al, 2007;Cohen-Mansfield et al, 2005) . Reports also suggest using BTSs does not definitively heighten the clinical health risk for preterm birth, bacterial vaginosis, hemorrhoids, or urogenital infections (Asakura et al, 2013;Kiuchi et al, 2017) .…”
Section: Introductionmentioning
confidence: 99%